2015
DOI: 10.1097/iae.0000000000000526
|View full text |Cite
|
Sign up to set email alerts
|

Initial Versus Delayed Photodynamic Therapy in Combination With Ranibizumab for Treatment of Polypoidal Choroidal Vasculopathy

Abstract: Both initial and deferred PDT combined with IVR to treat polypoidal choroidal vasculopathy show the similar visual and anatomical improvements at 12 months. Initial PDT combination leads to significantly fewer additional treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
93
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(100 citation statements)
references
References 38 publications
5
93
1
1
Order By: Relevance
“…Furthermore, initial PDT in combination with ranibizumab may lead to significantly fewer additional treatments 16. In our cohort, there was no significant reduction in the number of treatments required in patients who received PDT.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Furthermore, initial PDT in combination with ranibizumab may lead to significantly fewer additional treatments 16. In our cohort, there was no significant reduction in the number of treatments required in patients who received PDT.…”
Section: Discussionmentioning
confidence: 59%
“…More recently, it has been shown that both initial and deferred PDT combined with intravitreal ranibizumab show similar visual and anatomical improvements at 12 months in patients with PCV 16. Furthermore, initial PDT in combination with ranibizumab may lead to significantly fewer additional treatments 16.…”
Section: Discussionmentioning
confidence: 99%
“…15 Moreover, reports of the posttreatment prognosis of PCV patients are inconsistent among clinical studies. [16][17][18][19][20][21] For example, a randomized study (the EVEREST study) compared the efficacy of IVR and photodynamic therapy (PDT) for the treatment of PCV and concluded that the latter was more effective in achieving polyp regression. 16 In contrast, another study (the LAPTOP study) showed that IVR monotherapy was superior to PDT.…”
mentioning
confidence: 98%
“…Sato et al [10] also reported that combination therapy with PDT and bevacizumab injection for PCV was effective for improving BCVA and reducing retreatment rates and complications. The Fujisan study was a randomized prospective study designed to assess the timing of PDT, by comparing initial and deferred PDT combined with intravitreal ranibizumab [11] . Although BCVA change and polyp regression rate did not differ significantly between the groups, the ranibizumab injection number for 1 year in the initial PDT group was significantly lower compared to the deferred PDT group.…”
mentioning
confidence: 99%